Import of ADP/ATP carrier into mitochondria: two receptors act in parallel (The Rockefeller University Press, 1990)
We have identified the yeast homologue of Neurospora crassa MOM72, the mitochondrial import receptor for the ADP/ATP carrier (AAC), by functional studies and by cDNA sequencing. Mitochondria of a yeast mutant in which the gene for MOM72 was disrupted were impaired in specific binding and import of AAC. Unexpectedly, we found a residual, yet significant import of AAC into mitochondria lacking MOM72 that occurred via the receptor MOM19. We conclude that both MOM72 and MOM19 can direct AAC into mitochondria, albeit with different efficiency. Moreover, the precursor of MOM72 apparently does not require a positively charged sequence at the extreme amino terminus for targeting to mitochondria.